Abnormal scar identification with spherical-nucleic-acid technology. (April 2018) - Yeo, David; Wiraja, Christian; Paller, Amy; Mirkin, Chad; Xu, Chenjie
Abstract The accurate diagnosis of scar type and severity relies on histopathology of biopsied tissue, which is invasive and time-consuming, causes discomfort and may exacerbate scarring. Here, we show that imaging nanoprobes for the live-cell detection of intracellular messenger RNA (mRNA) (also known as NanoFlares) enable measurements of the expression of connective tissue growth factor (CTGF) as a visual indicator of hypertrophic scars and keloids. During cell culture, NanoFlares enabled the distinction of hypertrophic and keloidal fibroblasts from normal fibroblasts, and the detection of changes in CTGF expression resulting from the regulatory effects of transforming growth factor-β (TGF-β) agonists and TGF-β antagonists. We also applied the NanoFlares topically to the skin of live mice and rabbits, and to ex vivo human skin models. Transepidermal penetration of the NanoFlares enabled the visual and spectroscopic quantification of underlying abnormal fibroblasts on the basis of CTGF mRNA expression. Our proof-of-concept studies of topically applied NanoFlare technology as a means of biopsy-free scar diagnosis may eventually inform therapeutic decisions on the basis of the mRNA-expression patterns of skin disorders. Topically applied imaging nanoprobes for the detection of intracellular mRNA expression from connective tissue growth factor enable the detection of hypertrophic scars and keloids in the skin of small live animals and in ex vivo human skin.